2012
DOI: 10.1093/nar/gks1438
|View full text |Cite
|
Sign up to set email alerts
|

rDNA-directed integration by an HIV-1 integrase—I-PpoI fusion protein

Abstract: Integrating viral vectors are efficient gene transfer tools, but their integration patterns have been associated with genotoxicity and oncogenicity. The recent development of highly specific designer nucleases has enabled target DNA modification and site-specific gene insertion at desired genomic loci. However, a lack of consensus exists regarding a perfect genomic safe harbour (GSH) that would allow transgenes to be stably and reliably expressed without adversely affecting endogenous gene structure and functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…For example, for HIV-1 based vectors, it has been demonstrated that by modifying the DNA-binding capabilities of the IN cofactor protein LEDGF/p75, native LV integration preferences can be altered [7][8][9]. We have also shown that LV integration into a predetermined site can be increased significantly with the aid of IN-fusion proteins [10].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…For example, for HIV-1 based vectors, it has been demonstrated that by modifying the DNA-binding capabilities of the IN cofactor protein LEDGF/p75, native LV integration preferences can be altered [7][8][9]. We have also shown that LV integration into a predetermined site can be increased significantly with the aid of IN-fusion proteins [10].…”
Section: Introductionmentioning
confidence: 87%
“…We took IN-fusion proteins into modern third-generation LVs and showed that they could be used for the delivery of desired proteins into transduced cell nuclei [13]. Moreover, such vectors were able to enrich vector integration in predetermined genomic safe harbor target sites when IN was fused to a meganuclease recognizing a sequence at these sites [10]. This chapter describes the original design of IN-fusion protein-encoding constructs which drive the packaging of the proteins into thirdgeneration LV particles that can be used to study targeted integration or protein transduction.…”
Section: Introductionmentioning
confidence: 99%
“…Correct packaging of the IN-I-PpoI H78A into LVVs was verified by immunoblotting using an antibody against HIV-1 IN, as described previously [10]. VSV-G pseudotyped third generation LVVs were produced, concentrated, and titered with p24 ELISA and flow cytometry as described [8].…”
Section: Methodsmentioning
confidence: 99%
“…Due to the wealth of recognition sites and robust lentiviral transfer of the protein cargo, delivery of I-PpoI was found to be cytotoxic in a manner dependent on the enzyme activity. 111,112 However, by fusing the integrase to a mutated catalytically inactive I-PpoI variant, it was possible to promote targeted lentiviral insertions into ribosome RNA genes. 111 It is important to note also that vectors carrying an integrase fusion protein maintained the capacity to transfer vector RNA.…”
Section: Adapting Lentiviruses For Direct Protein Deliverymentioning
confidence: 99%
“…111,112 However, by fusing the integrase to a mutated catalytically inactive I-PpoI variant, it was possible to promote targeted lentiviral insertions into ribosome RNA genes. 111 It is important to note also that vectors carrying an integrase fusion protein maintained the capacity to transfer vector RNA. 110 Our own endeavors to develop lentiviral protein transduction for genome engineering were directed first at incorporating the hyperactive piggyBac transposase hyPBase 113 in lentiviral particles.…”
Section: Adapting Lentiviruses For Direct Protein Deliverymentioning
confidence: 99%